Analyses of trajectory on-the-fly based on the global reaction route map. Issue 3 (20th December 2017) - Tsutsumi, Takuro; Harabuchi, Yu; Ono, Yuriko; Maeda, Satoshi; Taketsugu, Tetsuya
Abstract : A methodology to analyze a trajectory on-the-fly (TOF) based on a global reaction route map consisting of intrinsic reaction coordinate (IRC) pathways is proposed. Abstract : A methodology to analyze a trajectory on-the-fly (TOF) based on a global reaction route map consisting of intrinsic reaction coordinate (IRC) pathways is proposed. By using the distance functions in the configurational space, the location of each point on the trajectories is detected, providing a dynamical picture that the molecular system goes over several minima and transition states in the reaction path network. In its application to structural transformations of an Au5 cluster, a variety of reaction routes are obtained, and the hopping from one IRC to another IRC (IRC-jump) is analyzed. The branching of trajectories over many minima on the potential energy surface via valley-ridge transition points is also discussed.